C-Doped KNbO3 single crystals for enhanced piezocatalytic intermediate water splitting. Issue 6 (12th April 2022) - He, Jiaqing; Gao, Feng; Wang, Haowei; Liu, Fangyan; Lin, Jiahui; Wang, Biao; Liu, Chuan; Huang, Feng; Lin, Zhang; Wang, Mengye
Abstract : Through the intermediate water splitting reaction, H2 O is simultaneously and efficiently converted into H2 O2 and H2 using C-doped KNbO3 as the catalyst via a green and sustainable piezocatalytic technique. Abstract : H2 O2 is an environmentally friendly chemical for wide water treatments and H2 is regarded as an ideal substitute for traditional fossil energy. The industrial production of H2 O2 is via the anthraquinone oxidation process, which, however, consumes extensive energy and produces pollution. Herein, based on the density functional theory (DFT) calculations, we report a green and sustainable piezocatalytic intermediate water splitting (IWS) process to simultaneously obtain H2 O2 and H2 using C-doped KNbO3 nano single crystals as catalysts. The KNbO3 catalysts doped with suitable amounts of carbon show an enhanced water splitting rate, which could be attributed to the decreased reaction barriers on the C-KNbO3 surface and improved polarized built-in electric field, as evidenced by DFT simulations and PFM measurements. Remarkably, the piezocatalytic H2 evolution efficiency of 0.5 : 1 C-KNbO3 reaches 524.51 μmol g −1 h −1 . Additionally, 0.5 : 1 C-KNbO3 could generate H2 and H2 O2 simultaneously through two-electron piezocatalytic IWS reactions. This improved catalytic efficiency is attributed to the promoted piezo-response of KNbO3 after C doping, as revealed by PFM tests.